PENERAPAN STRATEGI PEMECAHAN MASALAHUNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII5 SMP NEGERI 4 PEKANBARU - Fikri, Yomaysha Jasmia; Saragih, Sehatta; Suhermi, Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The type of this research is Classroom Action Research with two cycles. This research conducted of class VII5 SMPN 4 Pekanbaru on secons semester of academic year 2017/2018 wich consists of 35students. This study aims to improve the learning process and improve the student’smathematical problem solving skill (MPSS) by applying Problem Solving Strategy (PSS). The instruments used in this research were learning instrumentsused include syllabus, lesson plan, student work sheets and the instruments of collecting data were observation sheets and MPPS test. After analysis of implementing the Problem Solving Strategy on students and teacher activity, during the learning process student’s participation in learnig more active. The MPSS test data of analyzed students’activity shows an improvement. The mean of the student’s learning achievmentfor scores early 49.72 increase in cycle I which is 68.86 had improved to 85.31in cycle II. This study concludes that the implementation of PSScan improve learning process and student’s MPSS at class VII5 SMPN 4 PekanbaruKey Words: Problem Solving Strategy, mathematical problem solving ability, class action research